Risk Factors of Hypertension among Women in Sragen, Central Java - Sudaryanto Sudaryanto; Setyo Sri Rahardjo; Dono Indarto (Journal of Epidemiology and Public Health, 2019)
Background: Hypertension has become a global problem because its prevalence continues to increase to the stage of worrying. Health profile data of Sragen District Health Office in 2014 showed that out of 175,750 people aged >18 years who took blood pressure measurement, there were 28.73% (50,499 people) identified as having high blood pressure and 25,928 of them were women. This study aimed to examine the risk factors of hypertension among women in Sragen, Central Java, Indonesia.Subjects and Method: This was a case-control study conducted in Sragen, Central Java. The total sample of 200 women was selected by fixed disease sampling. The dependent variable was hypertension. The independent variables were age, history of hypertension, stress, smoking, physical activity, alcohol consumption, salt consumption, coffee consumption, body mass index (BMI), and cholesterol level. Blood pressure was measured by sphygmomanometer. The other data were measured by questionnaire. The data were analyzed by multiple logistic regression.Results: Age ?40 years (OR= 5.27; 95% CI= 1.81 to 15.28; p= 0.002), had history of hypertension (OR= 4.75; 95% CI= 1.46 to 15.39; p= 0.009), stress (OR= 5.32; 95% CI= 1.50 to 18.84; p= 0.009), smoking (OR= 17.51; 95% CI= 1.18 to 258.70; p= 0.037), low physical activity (OR= 7.89; 95% CI= 2.44 to 25.51; p = 0.001), alcohol consumption (OR= 23.06; 95% CI= 1.49 to 335.39; p= 0.025), salt consumption (OR= 16.68; 95% CI= 1.61 to 172.83; p= 0.018), coffee consumption (OR= 4.19; 95% CI= 1.03 to 16.98; p= 0.045), BMI (OR= 5.60; 95% CI= 1.23 to 9.71; p= 0.018), high total cholesterol (OR= 6.49; 95% CI = 2.00 to 21.05; p = 0.002) increased the risk of hypertension among women. Nagelkerke R Square= 72.2%.Conclusion: Age ?40 years, history of hypertension, stress, smoking, low physical activity, alcohol consumption, salt consumption, coffee consumption, BMI, high total cholesterol increase the risk of hypertension among women.Keyword: hypertension, determinants, womenCorrespondence: